2013
DOI: 10.1208/s12249-012-9891-3
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Recrystallized Caffeine on Water-Swellable Polymethacrylate Mucoadhesive Buccal Films

Abstract: The aim of this work was to investigate the influence of particles on the properties of polymethacrylate films intended for buccal delivery. A solvent casting method was used with Eudragit RS and RL (ERS and ERL, respectively) as film-forming rate-controlling polymers, with caffeine as a water-soluble model drug. The physicochemical properties of the model films for a series of formulations with increasing concentrations of caffeine were determined in terms of morphology, mechanical and mucoadhesive properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…ERS and ERL are more commonly known for their applications in sustained drug delivery by controlling drug release rate of dosage forms. However, more recently we have reported on the high mucoadhesive properties exhibited by polymethacrylates and, more specifically, ERL . In accordance with our previous findings, films containing ERL showed high or very high mucoadhesive properties.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…ERS and ERL are more commonly known for their applications in sustained drug delivery by controlling drug release rate of dosage forms. However, more recently we have reported on the high mucoadhesive properties exhibited by polymethacrylates and, more specifically, ERL . In accordance with our previous findings, films containing ERL showed high or very high mucoadhesive properties.…”
Section: Resultssupporting
confidence: 90%
“…However, most of these investigations led to particles in the range of 1–5 μm or higher. To guarantee physical stability of the films in terms of both mechanical and mucoadhesive properties, such large particles are undesirable due to the potential for aggregation and loss in active distribution homogeneity . Our group has recently described the manufacture of submicron and nanosized particles of lysozyme (Lys)‐loaded d , l ‐valine (Val), also known as protein‐coated nanoparticles (PCNPs), and the advantages of this method of manufacture to provide high loading efficiency and enzymatic stability .…”
Section: Introductionmentioning
confidence: 99%
“…An ideal buccal film should be flexible, elastic, soft but adequately strong to withstand breakage due to the stress of mouth activities (Szabó et al, 2013). Therefore, films displaying relatively high tensile strength and elongation at break are preferred for such application (Morales et al, 2013). In this work, as it was mentioned above, the elongation at break was reduced when CH was combined with carrageenans and even more when the number of anionic charges in carrageenans was increased (Fig.…”
Section: Films' Thickness Folding Endurance and Mechanical Propertiesmentioning
confidence: 62%
“…21) The mucoadhesiveness is brought about by the non-covalent bonding between mucin and substances. 22,23) For example, it is reported that the mucoadhesion of the guar gum is caused by the interaction between its hydroxyl groups and the mucin's carbonyl groups. 23) In addition, though it is reported that HPMC has muco-adhesiveness to mucin due to the interaction between HPMC's hydroxyl group and mucin, the extent of their interaction is weaker than that of carbopol, a known mucoadhesive polymer.…”
Section: Resultsmentioning
confidence: 99%